2022
DOI: 10.1097/cad.0000000000001407
|View full text |Cite
|
Sign up to set email alerts
|

Combination toripalimab and bevacizumab for an elderly urothelial carcinoma patient with brain metastasis who failed rapidly after radiotherapy: a case report and literature review

Abstract: Brain metastasis is a rare refractory event in patients with urothelial carcinoma. Platinum-based chemotherapy is the recommended first-line standard therapy for all metastasis urothelial carcinoma patients eligible for cisplatin or carboplatin. Patients ineligible for platinum may receive immunotherapy. No clear evidence exists that UC with brain metastasis is sensitive to immunotherapy, and the optimal treatment for patients with BM is uncertain. We evaluated the safety and efficacy of combined immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The demand for more effective treatment options is apparent based on the poor prognosis currently reported for patients with BTCs [15]. With the rapid development of ICIs, which can activate effector T cells and increase the cytotoxicity and infiltration of effector T cells to normalize tumor vasculature [16], several trials of combining ICIs with chemotherapy are underway, such as KEYNOTE-966, ABC-02, and TOPAZ-1 [17]. However, patients with recurrent or advanced BTCs often experience a rapid decline in performance status, and cannot tolerate chemotherapy [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for more effective treatment options is apparent based on the poor prognosis currently reported for patients with BTCs [15]. With the rapid development of ICIs, which can activate effector T cells and increase the cytotoxicity and infiltration of effector T cells to normalize tumor vasculature [16], several trials of combining ICIs with chemotherapy are underway, such as KEYNOTE-966, ABC-02, and TOPAZ-1 [17]. However, patients with recurrent or advanced BTCs often experience a rapid decline in performance status, and cannot tolerate chemotherapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…Toripalimab, a humanized IgG4K mAb against PD-1, has a high binding affinity. A study showed the different binding orientation of toripalimab compared with other ICIs, which binds PD-1 mainly on a loop that contributes to multiple interactions with programmed death-ligand 1 [16,19]. Sheng et al [20] reported the good tolerability of toripalimab, which may make it possible to use concurrently with other anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%